Transformasi Tasawuf Urban: Peran Musik dan Zikir dalam Pembentukan Identitas Spiritual Muslim Indonesia - Dea Nur Fatimah; Fajar Al Kautsar; Sobirin (STKIP Subang, 2025)
Sufism is an essential dimension of Islam that emphasizes spiritual development through dhikr, self-discipline, and the purification of the soul. Within the context of urban Indonesian society, Sufi practices have undergone significant transformation due to modernization, urbanization, and the dynamics of urban culture. Music (samāʿ) and dhikr have emerged as central media in spiritual experiences while simultaneously shaping the religious identity of urban Muslims that is moderate, reflective, and contextually grounded. This study aims to analyze the transformation of urban Sufism in Indonesia, particularly the role of music and dhikr in shaping the spiritual identity of twenty-first-century Muslims. The research employs a library research method by examining scholarly literature, including books, journal articles, undergraduate theses, master’s theses, and dissertations addressing Sufism, spiritual music, dhikr, and religious identity within urban contexts. The data are analyzed thematically to illustrate changes in Sufi practices and the role of music and dhikr in spiritual experience and identity formation among urban Muslims. The findings indicate that urban Sufism has evolved into a more open, inclusive, and communicative practice. Music and dhikr function as contemplative and psychospiritual media that help participants manage stress and anxiety while enhancing inner tranquility. The integration of music and dhikr also contributes to the formation of urban Muslim spiritual identity, strengthens social solidarity, and creates a balance between worldly engagement and inner spirituality. Despite criticism from puritan groups, urban Sufism demonstrates resilience through cultural and educational approaches that remain relevant to modern and digital life.